Echocardiography - Feigenbaum, Harvey (Lea and Febiger, 1986)
The thoroughly revised Sixth Edition of Feigenbaum\'s Echocardiography reflects recent changes in the technology and clinical use of echocardiography. Included are detailed discussions of tissue Doppler imaging, harmonic imaging and its impact on tissue and contrast visualization, new applications of myocardial perfusion and three-dimensional echocardiography. Emphasizing the clinical importance of various echocardiography applications, this edition has chapters on systolic and diastolic left ventricular function, infective endocarditis, prosthetic valves, contrast echocardiography, stress echocardiography, systemic diseases, and operative and perioperative echocardiography. More than 1,200 illustrations complement the text. An accompanying DVD-ROM contains more than 900 moving cine loops with corresponding still images from the book.
Keywords: kardiologie; echokardiografie; angiologie; Echocardiography